Common Purslane Biology and Control in Fruiting Vegetables, Cucurbits, and Small Fruits - Andrew W. MacRae (EDIS, 2010)
HS1173, a 3-page illustrated fact sheet by Andrew W. MacRae, describes this drought resistant annual with succulent leaves found in most habitats in Florida — classification, seedling identification, mature plant, management considerations, and chemical control. Includes references. Published by the UF Department of Horticultural Sciences, May 2010.